Lichenoid Keratosis: A Clinical Trap without Secrets for Reflectance Confocal Microscopy - Sara Mazzilli; Terenzio Cosio; Elena Campione; Salvador Gonzalez; Caterina Lanna; Monia Di Prete; Virginia Velasco; Luca Bianchi (Karger Publishers, 2020)
Lichenoid keratosis, also defined as benign lichenoid keratosis, was reclassified as lichen planus-like keratosis by Shapiro and Ackerman. Clinical and dermoscopic features of lichen planus-like keratosis can vary, often not providing useful and necessary information to perform an accurate diagnosis without performing a biopsy or histological examination. We describe 2 difficult to detect lichen planus-like keratosis cases in which we performed reflectance confocal microscopy. We underline the usefulness of this noninvasive diagnostic tool in the unclear cases of lichen planus-like keratosis.